2010
DOI: 10.1111/j.1541-0064.2009.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

A geographic assessment of ‘total’ health care supply in Ontario: complementary and alternative medicine and conventional medicine

Abstract: A geographic assessment of 'total' health care supply in Ontario 105 in the province. CM specialization is rarer and is biased towards the more populated municipalities. Third, a Spearman's correlation analysis suggests that CAM and CM health care supply are associated with community well-being indictors and urban density measures. Key words: complementary and alternative medicine (CAM), health care, physicians, medical geography province canadienne d'Ontario. L'analyse est réalisée en trois temps. Primo, les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Where primarily privately-funded, market-driven healthcare resources are concerned, previous studies have shown that as economic prosperity increases, so does the likelihood that the area will have a higher per capita level of privately-funded healthcare supply (Kruger et al, 2012;Meyer, 2009), and while the results of the analysis conducted here broadly indicate that the inverse may be also true in the case of osteopathic clinics, further research is required to determine if this is the case.…”
Section: Spatial Pattern Analysesmentioning
confidence: 75%
See 3 more Smart Citations
“…Where primarily privately-funded, market-driven healthcare resources are concerned, previous studies have shown that as economic prosperity increases, so does the likelihood that the area will have a higher per capita level of privately-funded healthcare supply (Kruger et al, 2012;Meyer, 2009), and while the results of the analysis conducted here broadly indicate that the inverse may be also true in the case of osteopathic clinics, further research is required to determine if this is the case.…”
Section: Spatial Pattern Analysesmentioning
confidence: 75%
“…The results of this analysis were merged with digital maps containing census-derived attributes of the area, such as average incomes, employment rates and population density, before Spearman's correlation analyses of the relationship between clinic distribution and social aspects of the environment were measured. The results of this study suggested that as economic prosperity increased, so did the likelihood that the area would have a higher per capita level of CAM healthcare supply (Meyer, 2009). A limitation of this study is that the geographic units of measurement reported are census subdivisions, which are essentially municipalities (Meyer, 2009).…”
Section: Potential Factors Influencing the Geographic Accessibility Omentioning
confidence: 84%
See 2 more Smart Citations
“…Collectively these CSDs display a provincial pattern that provides further evidence that the location choices of acupuncture office practitioners are, in some ways, distinguishable from the more general CAM situation. Meyer (2010) found that CAM specialization in Ontario was wide-spread and prevalent in all four provincial districts and quite evenly distribution across the urban-peripheral continuum (in comparison to conventional medical offices). In contrast, it is very rare for communities to specialize in acupuncture.…”
mentioning
confidence: 96%